AGAMA DAN KEBUDAYAAN DALAM PERSPEKTIF FILSAFAT HERMENEUTIS - Donatus Sermada Kelen (Litbang STFT Widya Sasana Malang, 2002)
The article contains a philosophical approach adopted by the author in his effort to apply this method to understand and to interprete the meaning of “Religion and Culture“. The philosophical approach the author would like to focuse on is the hermeneutical philosophy. The author describes first the general view of the hermeneutical philosophy in the light of the historical development, especially the ideas of some important philosophers who were dealing systematically with the hermeneutics, and then the author tries to apply the hermeneutics to the field of religion and of culture in the separated way. The last part of the article is concentrated on the theme of how to understand and to interprete the meaning of religion and culture unseparatedly.